2007
DOI: 10.1159/000100772
|View full text |Cite
|
Sign up to set email alerts
|

Utility of the Bender Gestalt Test for Differentiation of Dementia with Lewy Bodies from Alzheimer’s Disease in Patients Showing Mild to Moderate Dementia

Abstract: Aims: We examined the utility of the Bender Gestalt Test (BGT) for the differentiation of dementia with Lewy bodies (DLB) from Alzheimer’s disease (AD), comparing BGT scores between DLB and AD patients showing mild to moderate dementia. Methods: Eighteen DLB patients, 36 AD patients controlled by age, years of education, Clinical Dementia Rating and Mini Mental State Examination scores, and 21 nondemented elderly participants controlled by age and years of education were subjected to the BGT. Their BGT perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 59 publications
1
13
0
Order By: Relevance
“…This may be due to the fact that the clinical conditions corresponding to MCI of DLB or FTLD have not been defined. DLB patients show characteristic visuoperceptual and/or constructional disabilities (Moshiman et al, 2004;Murayama et al, 2007). In the present study, Case 11 fulfilled the diagnostic criteria for probable DLB (McKeith et al, 1996(McKeith et al, , 2005, while Case 12 showed memory impairment and REM sleep disorder, one of the suggestive features of DLB, as well as visuoperceptual disability, suggesting that he may progress to DLB (MCI of DLB).…”
Section: F-fdg Pet Images Of Patientssupporting
confidence: 55%
See 1 more Smart Citation
“…This may be due to the fact that the clinical conditions corresponding to MCI of DLB or FTLD have not been defined. DLB patients show characteristic visuoperceptual and/or constructional disabilities (Moshiman et al, 2004;Murayama et al, 2007). In the present study, Case 11 fulfilled the diagnostic criteria for probable DLB (McKeith et al, 1996(McKeith et al, , 2005, while Case 12 showed memory impairment and REM sleep disorder, one of the suggestive features of DLB, as well as visuoperceptual disability, suggesting that he may progress to DLB (MCI of DLB).…”
Section: F-fdg Pet Images Of Patientssupporting
confidence: 55%
“…He revealed visuoperceptual disability in the Bender gestalt test (Murayama et al, 2007). His MRI examination exhibited mild atrophy of the hippocampus.…”
Section: Clinical Neuropsychological Mri Findings and 18 F-fdg Petmentioning
confidence: 98%
“…Patient 4 scored 25 points on the MMSE (recent memory 2/3, attention 3/5, construction 0/1). On the BGT, Patient 4 scored 106 points, indicating a visuoperceptual impairment that met the threshold score for patients with probable DLB 22 . In the group without occipital hypometabolism, the cognitive scores were within the normal range on the MMSE, WMS‐R, and WAIS‐III.…”
Section: Resultsmentioning
confidence: 99%
“…The Clinical Dementia Rating (CDR), Mini‐Mental State Examination (MMSE), Wechsler Memory Scale‐Revised (WMS‐R), and Wechsler Adult Intelligence Scale‐III (WAIS‐III) provided cognitive measures. The Bender Gestalt Test (BGT) was performed to assess visuospatial faculties 22 …”
Section: Methodsmentioning
confidence: 99%
“…After this age, other factors seem to have more infl uence on the score. In childhood and during later stages of maturity, it is used to assess manifestations of pathology or physical, psychological, or social risk ( Cousino & Wilder, 1978 ;Shapiro & Simpson, 1995 ;Romi & Marom, 2005 ;Murayama, Iseki, Yamamoto, Kimura, Eto, & Arai, 2007 ;Santos & Jorge, 2007 ;Sheikhi, 2007 ;Pacanaro, Santos, & Suehiro, 2008 ;Vendemiatto, Santos, & Suehiro, 2008 ;Silva, Feil, Souza, & Paniagua, 2009 ;Böhm, Lundequist, & Smedler, 2010 ;Sardinha, 2011 ).…”
mentioning
confidence: 99%